4-Azatricyclo[5.2.2.02,6]undecane-3,5,8-triones as Potential Pharmacological Agents - Marta Struga; Izabela DybaÅa; Anna E. KozioÅ; Barbara MirosÅaw; Anna Bielenica; Jerzy Kossakowski (Molecules, 2008)
A series of twenty six arylpiperazine and aminoalkanol derivatives of 4-azatricyclo[ 5.2.2.02,6]undecane-3,5,8-trione have been prepared. The synthesized compounds were evaluated for their cytotoxicity and anti-HIV-1 activity in MT-4 cells.